Meningkatkan Kemampuan Bahasa Reseptif Melalui Kegiatan Cerita Berbasis Karakter pada Anak - Adelina Silitonga; Dewi Fitria (Pusat Riset dan Inovasi Nasional, 2025)
The improvement of receptive language skills in early childhood is still relatively low because this period is the early stage of learning. Children at an early age need the right stimulation to develop an understanding of spoken language, including listening, understanding, and responding appropriately. This research aims to improve receptive language skills through character-based storytelling activities in group B children at Kemala Bhayangkari Tanjung Morawa Kindergarten. The method used is Class Action Research (PTK) with two cycles, each consisting of stages of planning, implementation, observation, and reflection. The study subjects consisted of 20 children (10 boys and 10 girls) with homogeneous age characteristics. Data was collected through observation, assignment, and documentation techniques. Character-based story activities are carried out using visual media and interesting character narratives to stimulate children's imagination and captivity. The results of the study showed a significant improvement in children's receptive language skills. The percentage of children in the Undeveloped (BB) and Starting to Develop (MB) categories decreased drastically, while the Developing Expectations (BSH) and Very Good Developed (BSB) categories increased significantly. Children become more active in responding to stories, able to repeat sentences heard, understand simple commands, and show a higher interest in reading activities. In addition, character-based story activities have a positive impact on children's social-emotional development, because they learn to recognize the moral values of the story characters, such as honesty, courage, and responsibility. Verbal interaction between teacher and child increases, strengthens interpersonal relationships and creates a more communicative and supportive learning environment. Children also showed a better ability to relate stories to their own experiences, which is an indicator of improved critical thinking skills and language comprehension.